Plakophilin-1, a Novel Wnt Signaling Regulator, Is Critical for Tooth Development and Ameloblast Differentiation. - Kanako Miyazaki; Keigo Yoshizaki; Chieko Arai; Aya Yamada; Kan Saito; Masaki Ishikawa; Han Xue; Keita Funada; Naoto Haruyama; Yoshihiko Yamada; Satoshi Fukumoto; Ichiro Takahashi (PLoS ONE)
Tooth morphogenesis is initiated by reciprocal interactions between the ectoderm and neural crest-derived mesenchyme, and the Wnt signaling pathway is involved in this process. We found that Plakophilin (PKP)1, which is associated with diseases such as ectodermal dysplasia/skin fragility syndrome, was highly expressed in teeth and skin, and was upregulated during tooth development. We hypothesized that PKP1 regulates Wnt signaling via its armadillo repeat domain in a manner similar to β-catenin. To determine its role in tooth development, we performed Pkp1 knockdown experiments using ex vivo organ cultures and cell cultures. Loss of Pkp1 reduced the size of tooth germs and inhibited dental epithelial cell proliferation, which was stimulated by Wnt3a. Furthermore, transfected PKP1-emerald green fluorescent protein was translocated from the plasma membrane to the nucleus upon stimulation with Wnt3a and LiCl, which required the PKP1 N terminus (amino acids 161 to 270). Localization of PKP1, which is known as an adhesion-related desmosome component, shifted to the plasma membrane during ameloblast differentiation. In addition, Pkp1 knockdown disrupted the localization of Zona occludens 1 in tight junctions and inhibited ameloblast differentiation; the two proteins were shown to directly interact by immunoprecipitation. These results implicate the participation of PKP1 in early tooth morphogenesis as an effector of canonical Wnt signaling that controls ameloblast differentiation via regulation of the cell adhesion complex.